AFLP analysis of genetic similarity between the species of the genus Lolium - Polok, Kornelia; Ciągło, Sylwia; Cabrita, Luis (Biodiversity: Research and Conservation, 2006)
The genus Lolium is represented by selfpollinated L. loliaceum, L. persicum, L. remotum and L. temulentum and outpollinated L. multiflorum, L. perenne and L. rigidum. The aim of the present study was the analysis of phylogenetic relationships between all Lolium species on the base of AFLP markers. All Lolium species were analysed with 8 pairs of AFLP primers. Each pair of primers resulted in the amplification of large number of AFLP fragments. Most fragments were polymorphic and many of them were restricted to a single species. Only 10 fragments were monomorphic across all species tested. The UPGMA clustering grouped all species into two groups. The first group was represented by three selfpollinated species, L. persicum, L. remotum and L. temulentum while the second one is formed by three outpollinated species, i.e. L. multiflorum, L. perenne and L. rigidum. Out of these species, L. multiflorum and L. perenne are joined with the highest genetic similarity providing further credence to our earlier conclusion that both taxa can not be regarded as biological species. The grouping of L. loliaceum within outpollinated species may suggest that this taxon evolved within a group of outpollinated taxa, followed by several point mutations responsible for self-fertility.